KARAKTERISTIK SOSIAL EKONOMI PEREMPUAN PEDAGANG SAYUR DI PASAR INPRES MATAWAI DAN KONTRIBUSINYA DALAM PENDAPATAN RUMAH TANGGA - Anastasia Diana Megawati Tumimomor (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2017)
The increasing need for life and the lack of income is the reason for the wife to work. The most accessible areas of work are the informal sector, such as trading with small capital, opening stalls, housemaids and waitresses. The informal sector is an ideal choice for women and children under 18, as it does not require high diplomas, major capital and administrative processes such as the formal sector. Wanitamaster vegetables have many aspects interesting enough to be studied, because it can not be denied that today, almost all households no longer rely on the fulfillment of the needs of husband's income alone, and sustained by the wives. Could be, this also happens in Waingapu City, especially in women in Matawai Inpres Market. This study aims to: 1. Know the socio-economic characteristics of female vegetable peddlers in Pasar Inpres Matawai, Kec. Waingapu City. 2. Knowing the contribution amount of female vegetable seller income to household income. The determination of respondents in this study using purposive sampling technique with the criteria: Female vegetable sellers in Pasar Inpres Matawai married long business more than 1 year and have fixed stalls in the market. By using the sample calculation formula from Frank Lynch, obtained the number of samples as many as 40 people. The type of data used is primary and secondary data and the data is analyzed by quantitative descriptive technique. The result of the research concludes Social Characteristic of Women Vegetable Traders: a) Being in productive age group that is 25 to 40 years old; b) Generally married; c) Minimum education level of elementary - high school, d) Derived from outside East Sumba, West Sumba and Southwest Sumba, e) Has been in business for 3 years to 5 years without changing their business, f) Owner and business manager (self employed ) with an average of 17-18 hours per day. Economic Characteristics of Women Vegetable Traders: a) Requires relatively small capital under Rp 500,000, so the source of capital in general uses its own capital; b) The maximum number of female vegetable traders is 6 but many female vegetable traders have 4 dependents; c) Number of family members who work in general 1 person, namely husband; d) The type of work of family members who work in general in the informal sector as well, such as farmers, motorcycle taxis, sellers, and honorary employees; e) Husband's income ranges from Rp.600,000 to Rp 2,500,000 per month; f) Net income from vegetable trading business is quite low, which is below Rp 1,500,000 per month; g) Household income generally below Rp 3,000,000 per month, h) Household income per capita is generally below Rp 1,000,000 per month and Income from vegetable trading business contributes 65% of total household income.